International Certificate Course in Digital Agriculture - Gakhar, Shalini; Sharma, Sheetal; Patwar, Shelly; Arya, Satyajeet (2023)
The “International Certificate course in Digital Agriculture,” a collaborative capacity sharing initiative by CGIAR’s International Rice Research Institute, New Delhi, and Sri Sri University, Odisha, under the CGIAR Digital Innovation Initiative, was organized as an online diploma program aimed at bolstering the technical capacity of agricultural students and professionals. Spanning seven weeks and 40 hours, including assignments, this course uniquely catered to the needs of those passionate about digital agriculture (DA), offering comprehensive insights into digital technologies, user-centered design principles, and data analytics to foster informed decision-making in agri-food systems. Specifically tailored to accommodate the busy schedules of participants, the course facilitated weekend online learning, drawing a substantial interest with over 800 applicants from India and abroad. Following a robust selection process, 95 candidates, including 56 females and 39 males, enrolled on this course to deepen their understanding and competencies in DA, ensuring a more inclusive and technologically adept agricultural landscape.